Necrotic and inflammatory changes in metal-on-metal resurfacing hip arthroplasties. - Mahendra, G; Pandit, H; Kliskey, K; Murray, D; Gill, H; Athanasou, N (2009)
BACKGROUND: Necrosis and inflammation in peri-implant soft tissues have been described in failed second-generation metal-on-metal (MoM) resurfacing hip arthroplasties and in the pseudotumors associated with these implants. The precise frequency and significance of these tissue changes is unknown. METHOD: We analyzed morphological and immunophenotypic changes in the periprosthetic soft tissues and femoral heads of 52 revised MoM arthroplasties (fracture in 21, pseudotumor in 13, component loosening in 9, and other causes in 9 cases). RESULTS: Substantial necrosis was observed in the periprosthetic connective tissue in 28 of the cases, including all pseudotumors, and 5 cases of component loosening. A heavy, diffuse inflammatory cell infiltrate composed mainly of HLA-DR+/CD14+/CD68+ macrophages and CD3+ T cells was seen in 45 of the cases. Perivascular lymphoid aggregates composed of CD3+ cells and CD20+ B cells were noted in 27 of the cases, but they were not seen in all cases of component loosening or pseudotumors. Plasma cells were noted in 30 cases. Macrophage granulomas were noted in 6 cases of component loosening. In the bone marrow of the femoral head, a macrophage and T cell response was seen in 31 of the cases; lymphoid aggregates were noted in 19 of the cases and discrete granulomas in 1 case. INTERPRETATION: Our findings indicate that there is a spectrum of necrotic and inflammatory changes in response to the deposition of cobalt-chrome (Co-Cr) wear particles in periprosthetic tissues. Areas of extensive coagulative necrosis and a macrophage and T lymphocyte response occur in implant failure and pseudotumors, in which there is also granuloma formation. The pathogenesis of these changes is uncertain but it may involve both a cytotoxic response and a delayed hypersensitivity (type IV) response to Co-Cr particles.